Attitudes And Concerns of Primary School Principals Regarding Inclusive Education - Ξανθούλα, Τσιολπίδου; Μαρία, Πλατσίδου (Education Sciences, 2019)
The present study examined attitudes and concerns of primary school principals regarding the inclusion of Special Educational Needs (SEN) pupils into mainstream classes. Participants were 151 head teachers from Northern Greece. Results indicated overall slightly positive attitudes (M=3.48 in a scale 1-5) towards inclusion but rather negative when connected to the adequacy of trained personnel and specific knowledge. Principals also reported a medium level of concern (M=2.2 in a scale 1-4) mainly about issues related to funding, adequacy of trained personnel, administrative support and implementation issues. Further analysis revealed a strong positive correlation of attitudes and a negative correlation of concern to years of teaching and administrative experience as well as to the percentage of SEN pupils attending the mainstream school. In addition, attitudes were found to significantly correlate to school size and concern to differentiate across gender and type of school. The scores in the CIES scale and in two of its subscales significantly predicted attitude scores. According to participants ensuring adequacy of supporting personnel alongside proper training for principals and mainstream educators on SEN topics are the main prerequisites for inclusion to succeed.